American Head and Neck Society Endocrine Section clinical consensus statement: North American quality statements and evidence‐based multidisciplinary workflow algorithms for the evaluation and management of thyroid nodules. Issue 4 (18th December 2018) - Meltzer, Charles J.; Irish, Jonathan; Angelos, Peter; Busaidy, Naifa L.; Davies, Louise; Dwojak, Sunshine; Ferris, Robert L.; Haugen, Bryan R.; Harrell, Richard M.; Haymart, Megan R.; McIver, Bryan; Mechanick, Jeffrey I.; et al.
Abstract: Background: Care for patients with thyroid nodules is complex and multidisciplinary, and research demonstrates variation in care. The objective was to develop clinical guidelines and quality metrics to reduce unwarranted variation and improve quality. Methods: Multidisciplinary expert consensus and modified Delphi approach. Source documents were workflow algorithms from Kaiser Permanente Northern California and Cancer Care of Ontario based on the 2015 American Thyroid Association management guidelines for adult patients with thyroid nodules and differentiated thyroid cancer. Results: A consensus‐based, unified preoperative, perioperative, and postoperative workflow was developed for North American use. Twenty‐one panelists achieved consensus on 16 statements about workflow‐embedded process and outcomes metrics addressing safety, access, appropriateness, efficiency, effectiveness, and patient centeredness of care. Conclusion: A panel of Canadian and United States experts achieved consensus on workflows and quality metric statements to help reduce unwarranted variation in care, improving overall quality of care for patients diagnosed with thyroid nodules.